1983
DOI: 10.1002/jso.2930220410
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of preoperative CEA levels in the assessment of colorectal cancer patient stage

Abstract: In order to demonstrate a prognostic value of preoperative CEA levels, we have tried to define a correlation between CEA and histologic stage of tumor in 124 patients with colorectal carcinoma. CEA concentration has been evaluated by radioimmunologic assay and the histologic stage following Dukes' classification. The results show a 25.0% positivity rate for patients in stage A, 48.2% for stage B, 61.1% for stage C, and 85.7% for stage D. The mean CEA values are 7.8 ng/ml in the first group, 30.3 ng/ml in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…Previous studies by Midiri et al (13) and Chen et al (12) reported a different tendency of the serum CEA levels in CRC patients with advancing stage. Our results of the present study revealed that the lowest CEA level was observed in stage C, with significant differences from stages A and D. The impacts of patient number, age and gender was not taken into consideration as they could not be controlled in this analysis and there were no differences between them.…”
Section: A B C D Discussionmentioning
confidence: 85%
“…Previous studies by Midiri et al (13) and Chen et al (12) reported a different tendency of the serum CEA levels in CRC patients with advancing stage. Our results of the present study revealed that the lowest CEA level was observed in stage C, with significant differences from stages A and D. The impacts of patient number, age and gender was not taken into consideration as they could not be controlled in this analysis and there were no differences between them.…”
Section: A B C D Discussionmentioning
confidence: 85%
“…A possible correlation between LAP scores and CEA levels was tested with negative results. Walach Guterman Zaidman Kaufman Scharf The value of CEA as a marker which correlates with colorectal cancer staging has been discussed by Midri et ah [3], who find a relationship between CEA levels and cancer spread.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with colon cancer, preopera tive CEA values have correlated with disease stage and have been shown to have prognostic value and utility in staging [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The positive rate of serum CEA increases in parallel to the disease stage. Particularly high serum CEA levels are often found in patients with metastasis [3,4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%